Decades of Tight Fiscal Policy Have Left the Health Care System in Italy Ill-Prepared to Fight the COVID-19 Outbreak - Franz J. Prante; Alessandro Bramucci; Achim Truger (Intereconomics, 2020)
Although austerity was particularly strong in the aftermath of the economic crisis of 2008 and its consequences in the euro area, Italian fiscal policies have been characterised by tough consolidation periods ever since the 1990s.
Keywords: 330